Forced expression of human macrophage colony‐stimulating factor in CD34+ cells promotes monocyte differentiation in vitro and in vivo but blunts osteoclastogenesis in vitro. (6th March 2017) - Montano Almendras, Carmen P.; Thudium, Christian S.; Löfvall, Henrik; Moscatelli, Ilana; Schambach, Axel; Henriksen, Kim; Richter, Johan
Abstract: Objectives: Here, we tested the hypothesis that human M‐CSF (hM‐CSF) overexpressed in cord blood (CB) CD34 + cells would induce differentiation and survival of monocytes and osteoclasts in vitro and in vivo. Methods: Human M‐CSF was overexpressed in cord blood CD34 + cells using a lentiviral vector. Results: We show that LV‐hM‐CSF‐transduced CB CD34 + cells expand 3.6‐ and 8.5‐fold more with one or two exposures to the hM‐CSF‐expressing vector, respectively, when compared to control cells. Likewise, LV‐hM‐CSF‐transduced CB CD34 + cells show significantly higher levels of monocytes. In addition, these cells produced high levels of hM‐CSF. Furthermore, they are able to differentiate into functional bone‐resorbing osteoclasts in vitro. However, osteoclast differentiation and bone resorption were blunted compared to control CD34 + cells receiving exogenous hM‐CSF. NSG mice engrafted with LV‐hM‐CSF‐transduced CB CD34 + cells have physiological levels of hM‐CSF production that result in an increase in the percentage of human monocytes in peripheral blood and bone marrow as well as in the spleen, lung and liver. Conclusion: In summary, ectopic production of human M‐CSF in CD34 + cells promotes cellular expansion and monocyte differentiation in vitro and in vivo and allows for the formation of functional osteoclasts, albeit at reduced levels, without an exogenous source of M‐CSF, in vitro.